Nomogram to predict the risk of preterm birth before 37 weeks and 34 weeks in pregnant women with a short cervix. (17th December 2022) - Liu, Yingnan; Zhu, YuChun; Liu, Yu; Liu, Minghui; Zhang, Yueyi; Chen, Jun; Yang, Huixia
Abstract: Objectives: This study investigated the potential factors that predict the risk of preterm birth (PTB) in pregnancies with a short cervix. These factors were used to create nomogram, which might be highly sensitive tools to predict the incidence of PTB. Methods: This retrospective cohort study enrolled pregnancies with a short cervix from 1 January 2017 to 1 January 2018. The primary outcomes were preterm birth <37 and 34 weeks. Logistic regression model was used to identify potential predictors of PTB. The identified risk factors were used to establish nomograms, which were validated using the receiver operating characteristic (ROC) curve and calibration curve. Results: In the multivariate analysis, overweight or obesity, parity ≧3 times, twin pregnancy, in vitro fertilization and embryo transfer (IVF-ET), gestational age at first observation of short cervix, cervical length (CL) at first observation of short cervix, history of PTB, and autoimmune disease were found to be predictors of PTB <37 weeks, while twin pregnancy, gestational age at first observation of short cervix, CL of short cervix, history of PTB, and prepregnancy hypertension were predictors of PTB <34 weeks. The area under the ROC curve of the nomogram predicting PTB <37 weeks and PTB <34 weeks were 0.803 and 0.771, respectively. Both models showed good discrimination Conclusions: Gestational age at first observation of short cervix, CL of short cervix and other factors are strong predictors of PTB in pregnancies with a short cervix. Both nomograms showed good discrimination and calibration, and hence might be effective in predicting PTB for this population.